Sustainability Aspects of Administrative Process Management: A Case Study Analysis - László Buics; Boglárka Eisinger (Chemical Engineering Transactions)
This article offers a detailed analysis of the university enrollment process from a process management perspective, focusing on sustainability aspects like the social cost of carbon. The study utilizes process visualization techniques, such as P-Graphs, to explore how administrative processes can be optimized to reduce environmental impact while maintaining efficiency. Enrollment is a vital yet complex component of university operations, often neglecting sustainability in traditional management approaches. Through a case study, this research demonstrates how process visualization can identify inefficiencies in the enrollment process and suggest improvements. By incorporating P-Graphs, the study evaluates sustainability metrics like carbon costs, guiding decision-makers in reducing environmental harm. The findings reveal that the current enrollment system is unsustainable in terms of operating costs, human factors, and CO2 emissions. This research underscores the importance of integrating environmental considerations into administrative processes, showing that universities can enhance environmental performance while continuing to provide quality education by combining process management with sustainability principles.